2013
DOI: 10.1103/physrevlett.110.047004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from a Nodeless Gap todx2y2-Wave in UnderdopedLa2

Abstract: Using angle-resolved photoemission spectroscopy (ARPES), it is revealed that the low-energy electronic excitation spectra of highly underdoped superconducting and nonsuperconducting La(2-x)Sr(x)CuO(4) cuprates are gapped along the entire underlying Fermi surface at low temperatures. We show how the gap function evolves to a d(x(2)-y(2)) form with increasing temperature or doping, consistent with the vast majority of ARPES studies of cuprates. Our results provide essential information for uncovering the symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 28 publications
(36 reference statements)
10
69
1
Order By: Relevance
“…In contrast, at low temperatures (To45 K), there is a gap in the electronic spectra, that is, the peak position at k F remains below E F . A similar gap exists in LSCO up to 8% doping 4 14 or Coulomb disorder effects are present 15 . EDCs extracted from Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, at low temperatures (To45 K), there is a gap in the electronic spectra, that is, the peak position at k F remains below E F . A similar gap exists in LSCO up to 8% doping 4 14 or Coulomb disorder effects are present 15 . EDCs extracted from Fig.…”
Section: Resultsmentioning
confidence: 98%
“…R ecent low-temperature angle-resolved photoemission spectroscopy (ARPES) experiments on the underdoped cuprate superconductors indicate the presence of a fully gapped Fermi surface (FS) [1][2][3][4] ; even in the antiferromagnetic phase 5 . The natural candidates for opening such a gap are charge or spin density waves (SDW).…”
mentioning
confidence: 99%
“…[191,[341][342][343][344][345][346] On the electrondoped side, we have demonstrated that strong SDW order removes the holepocket from the nodal region in the underdoped system, and the total band gap (= ∆ 2 SDW + ∆ 2 dSC ) appears to be nodeless even though the underlying pairing maintains d-wave symmetry. [99,347] This explanation does not hold in the holedoped case, where a hole-pocket is present at any doping.…”
Section: Nodeless D-wave Gap Due To Competition With Sdwmentioning
confidence: 99%
“…Recent experiments on nanoscale YBCO islands have shown a small, but measurable, energy gap of size 20-40 µeV [172], which was subsequently theoretically identified to be due to a subdominant s-wave order supported on the island surfaces [173]. Gapped nodal quasiparticles have also been measured in the bulk in the deeply underdoped regime and seem to be connected to the pseudogap state above T c [174,175], but the origin of this gap is at present not understood. [153].…”
Section: D-wave Superconductorsmentioning
confidence: 99%